The Relationship between the Planning Fallacy and Estimates of Task Duration - Jun TAKAHASHI (AAOS Transactions)
The research examines the relationship between the planning fallacy and estimates of task duration. The planning fallacy refers to a prediction, in which people underestimate the time it will take to complete tasks, despite the knowledge that tasks have taken longer than planned tasks. This study tested two hypotheses concerning people’s predictions of task duration time. The first hypothesis is that good time managers accurately estimate task duration. Study1 attempts to analyze the relationship between the planning fallacy and time management by the time management behavior scale. The second is that a person with high levels of self efficacy does not tend to underestimate task duration time. Study2 attempts to analyze the relationship between the planning fallacy and self-efficacy by the generalized self efficacy scale. The result of study1 supported the first hypothesis slightly (r = .344), but study2 was unsupported (r = .103) the second hypothesis. This result suggests the possibility that those who tend to do time management improve the underestimation of task duration time. It will require more systematic research.